Management of Indian meal moth and maize weevil in stored popcorn using approved grain protectants - Gao, Nan (Kansas State University, 2018)
Spinosad, methoprene, deltamethrin, and deltamethrin plus methoprene, are approved in the United States for treating popcorn. The Indian meal moth, Plodia interpunctella (Hübner), and maize weevil, Sitophilus zeamais (Motschulsky) are two stored-product insects found in popcorn. The efficacy of spinosad and methoprene against P. interpunctella in popcorn were determined in laboratory and field studies. In the laboratory study, eggs (to represent first instars), third, and fifth instars of the laboratory strain of P. interpunctella were exposed to 0.7, 1.4, 2.8 ppm methoprene and 1 ppm spinosad treated popcorn, respectively, to assess larval or adult emergence. In the field study, untreated and treated popcorn samples were placed in vinyl mesh pouches with two mesh-opening sizes and were buried 5 cm below popcorn surface. Pouches with large mesh-opening were used to monitor natural insect infestation between May to October, 2017. Pouches with small mesh-opening were used to conduct laboratory bioassays to evaluate adult emergence of P. interpunctella from eggs after exposed to treated popcorn. Probe traps, food- and pheromone-baited traps, and sticky traps were used to monitor insects in storage bins and cleaning processing facility. The laboratory study showed that there was no P. interpunctella adults emerged from eggs, third, and fifth instars in methoprene treated popcorn during 6 month storage. However, methoprene did not reduce egg-to-larval survival. Larval and adult emergence in the spinosad treated popcorn was significantly lower than controls. Field study showed that there was no adult emergence in methoprene treated popcorn in most cases, and significantly lower adult emergence in spinosad treated popcorn compare to control. P. interpunctella larva was the major insect found in large pouches. The red flour beetle, Tribolium castaneum (Herbst), and P. interpunctella were primary insect species captured by probe traps, food- and pheromone-baited traps and sticky traps over the six months’ study. These results suggested that methoprene could reduce P. interpunctella adult emergence. Spinosad also effectively suppressed the infestation of P. interpunctella. The field strain of S. zeamais was exposed to spinosad (1 ppm), methoprene (0.7, 1.4, 2.8 ppm), deltamethrin (0.5, 1.0 ppm), and deltamethrin plus methoprene (0.5+1.25, 1.0+2.5 ppm) treated popcorn, respectively, for 1 to 336 h exposure time. Mortality was assessed at 0, 7, 14, and 21 d after transferring to clean popcorn except for methoprene treatments which only counted mortality at 0 d. Progeny and adult emergence were counted after 42 d incubation in clean or original popcorn, respectively. All insecticides showed no delay toxicity against S. zeamais adults. Spinosad caused 100% mortality of S. zeamais after 336-h exposure. Complete progeny reduction and highest adult emergence reduction at 168 h exposure. The highest mortality of S. zeamais was 67.1 and 70.5% in deltamethrin and deltamethrin plus methoprene treated popcorn, respectively. Methoprene showed limited efficacy against S. zeamais including low mortality, progeny reduction and high adult emergence. These results indicated that spinosad was effective against S. zeamais. It is necessary to combine other insecticides with deltamethrin and methoprene to control field strain of S. zeamais in stored popcorn.
Keywords: Methoprene; Spinosad; Deltamethrin; Plodia interpunctella; Sitophilus zeamais; Popcorn